LO17: Barriers and enablers that influence guideline-based care of geriatric falls patients presenting to the emergency department. (May 2019) - Parks, A.; Eagles, D.; Cheung, W.; Ge, Y.; Stiell, I.
Abstract : Introduction : Geriatric patients commonly present to the emergency department (ED) after a fall. Unfortunately, recent evidence suggests that ED physicians are poorly adherent to published ED-specific geriatric falls guidelines. This study applied a theoretical domains framework (TDF)-driven approach to systematically investigate barriers and enablers in the provision of guideline-based care to older patients presenting to the ED with a fall.Methods : From June to September 2017, semi-structured interviews of staff ED physicians practicing in Ontario, Canada were conducted and analyzed. An interview guide based on the TDF was used to capture 14 domains that may influence provision of guideline-based care. Interview transcripts were analyzed, and specific beliefs were generated by grouping similar responses. Relevant domains were identified based on frequencies of beliefs, existence of conflicting beliefs, and evidence of strong beliefs that would influence provision of guideline-based care.Results : Eleven interviews were conducted with practicing ED physicians. Thirty specific belief statements across 13 different TDF domains (all except Optimism) were identified as relevant. Overall, Ontario ED physicians are supportive of providing guideline-based care and believe it would lead to better outcomes for geriatric falls patients. Important barriers include knowledge, skills, time and workload constraints, and inconsistent allied health support.Conclusion : This study identified important barriers and enablers to provision of guideline-based care in geriatric ED falls patients. These results will help guide implementation of guidelines nationally and internationally, with a focus on improved knowledge dissemination, implementation of training interventions, and improvements in allied health coverage and supports.